ISB recommendations for skin-marker-based multi-segment foot kinematics. (26th August 2021) - Leardini, Alberto; Stebbins, Julie; Hillstrom, Howard; Caravaggi, Paolo; Deschamps, Kevin; Arndt, Anton
Abstract: The foot is anatomically and functionally complex, and thus an accurate description of intrinsic kinematics for clinical or sports applications requires multiple segments. This has led to the development of many multi-segment foot models for both kinematic and kinetic analyses. These models differ in the number of segments analyzed, bony landmarks identified, required marker set, defined anatomical axes and frames, the convention used to calculate joint rotations and the determination of neutral positions or other offsets from neutral. Many of these models lack validation. The terminology used is inconsistent and frequently confusing. Biomechanical and clinical studies using these models should use established references and describe how results are obtained and reported. The International Society of Biomechanics has previously published proposals for standards regarding kinematic and kinetic measurements in biomechanical research, and in this paper also addresses multi-segment foot kinematics modeling. The scope of this work is not to prescribe a particular set of standard definitions to be used in all applications, but rather to recommend a set of standards for collecting, calculating and reporting relevant data. The present paper includes recommendations for the overall modeling and grouping of the foot bones, for defining landmarks and other anatomical references, for addressing the many experimental issues in motion data collection, for analysing and reporting relevant results and finally for designing clinical and biomechanical studies in large populations by selecting the most suitable protocol for the specific application. These recommendations should also be applied when writing manuscripts and abstracts.